تأثير تقيم اداء اعضاء قنوات التوزيع في رضا الزبون–بحث ميداني - داود غسان قاسم; عبد الرحمن حسين هشام (Journal of Economics and Administrative Sciences, 2013)
Abstract The distribution is one of the elements of the marketing mix key by which companies can to deliver their products through private channels to all customers in right time and right place to check though in which the levels desired by customer satisfaction, the and purpose of the discussion dealt with the preparation of analytical studies to explain the impact of live performance of distribution channels in achieve customer satisfaction in industrial companies, as well as the diagnosis and the reality of the research variables in companies under study and describe the kind of relationship between changers Home on the one hand and the relationship between the variables sub on the other hand, representing the research community to State Company for the pharmaceutical industry and medical supplies - Samarra and the General Company for dairy products- Abu Ghraib, made up the sample (homogeneous non-laboratory) of (70) people, managers and assistants directors of sections in the units and departments and divided equally to each of all the companies, the researcher used methods statistical correlation simple linear (Spearman), and coefficient of simple linear regression (Simple Regression Coefficient), and as well as the use of (t-test) to test the significant simple correlation coefficient, and (f-test) to test the significant simple linear regression, to reach a number of conclusions, mainly managed departments of marketing be used to evaluate the performance of distribution channels, especially the productivity distribution channels because of their role in achieving customer satisfaction, while the most important recommendations of research that the Iraqi companies, industrial, if it wanted to achieve levels desired by customer satisfaction, it must increase attention to productivity distribution channels and by working on a comparison between the rate of productivity distribution channels owned by the rates of similar companies compete the other, and motivate and reward members, and improve the productivity of distribution channels, and address the problems and constraints faced by members of the channel, and increase the impact on the employment of all its capabilities and financial resources are optimized, which guarantees them more distribution channels (increasing opportunities for distribution of their products) to achieve the levels desired by customer satisfaction, which is one of the most important goals of industrial companies in Iraq.